Estudos de sedimentos do rio Passaúna, com ênfase na determinação de metais pesados - Bocalon, Tiago Silvestro (2007)
Passaúna River´s Hidrographic Bay, is used with the purpose of distributing water to approximately five hundred people living at Curitiba and Metropolitan Region. Anthropological activities, such as occupation and usage of soil in an irregular way, throwing non-treated domestic wastewater and the presence of the old controlled landfill called Lamenha Pequena nearby, led to the possibility of existing heavy metals contamination at Passaúna River. The present work had as main target, to analyse the sediments of Passaúna River for the evaluation of impacts caused by heavy metals to the local environment. Samples were collected in two stages: in the first stage, the samples were collected on March,2006 during a raining period and in the second stage, on September,2006 during an intense drought period. Five points were chosen as representative samples throughout Passaúna River, from the old controlled landfill to the entrance of the reservatory. Results revealed that seasonality has a direct influence over the aquatic system, altering mainly the results of granulometry and also the distribution of the elements in the sediment. The X-Ray analysis applied to an enrichment factor, showed that K and Mg concentrations are above the media concentration of such elements on earth´s crust, probably because of their wide application in agriculture sector. Co and Cr were detected and also enriched in point five (reservatory entrance). Ba was found only during the raining period at the downstream point of the old landfill. High concentrations of Pb were detected in all points collected and these concentrations varied between 268mg/kg to 493,5mg/kg, which ilustrates the presence of an anthropological contamination.